Pelatihan Senam Ibu Hamil Sebagai Upaya Meningkatkan Kesehatan Ibu Dan Janin - Adisty Dwi Treasa; Cakrawati R; Hilmiah Hilmiah; Susanti Susanti; Uswatun Insani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Pregnancy is a physiological process that requires the mother's physical and psychological readiness. Lack of physical activity during pregnancy can increase the risk of pregnancy-related complaints, labor complications, and maternal and fetal health problems. Prenatal exercise is a safe and beneficial form of physical activity that improves maternal fitness and supports fetal growth and development. This Community Service activity aims to increase the knowledge and skills of pregnant women regarding prenatal exercise as an effort to maintain maternal and fetal health. Implementation methods include counseling, demonstrations, practical training in prenatal exercise, and activity evaluation. The results of the activity indicate an increase in pregnant women's knowledge about the benefits of prenatal exercise, improved skills in performing correct exercise movements, and a decrease in physical complaints during pregnancy. This activity is expected to serve as a promotive and preventive effort to improve maternal and fetal health.